The role of the primary school teacher in curriculum development: a study of the Scottish and Zimbabwean practice - Khimbini, Vinah Violet (The University of Edinburgh, 1993)
The Scottish national curriculum is based on the aim that teaching methods used must be fitted to the stage of development of the children. Thus, the Scottish Consultative Council on Curriculum is tasked to develop guidelines for Scottish primary schools.
Keywords: Scotland; Zimbabwe; curriculum development; primary school; teacher; curriculum content; curriculum guidelines; primary education; Scottish National Curriculum; English language; Mathematics; Environmental Studies; Religious education; moral education; expressive art